Experimental study on rupture of prestressing steel strand subjected to tensile load. Issue 3 (2nd May 2018) - Tang, Baijian; Xu, Jinxing; Wang, Fei
Abstract : Collision, abrasion and explosion may cause the failure of a post-tensioning tendon or a stay cable on a cable-supported structure. To study the process of rupture of seven-wire steel strands subjected to dynamic axial tensile load, an experimental programme was conducted by using three types of strand specimens. These were strands without damage, strands with a peripheral notch and strands with a V-type notch. In the locally damaged strand specimens, a notch was machined into their outer spiral wires. The load–time curve during the rupture and the rupture time of wire in the undamaged and damaged strands were investigated. The specimens were tested under tension at different loading strain rates in order to determine the influence on the load–time history and the rupture time. Experimental results show that the loading rate has little influence on the rupture time for both undamaged and damaged strands, but has an obvious influence on the ultimate load of undamaged strands. For damaged strands, their ultimate load is affected by the notch to a large extent. The notch effect can be easily found by a tensile test. The results presented provide a basis for analysing the post-breakage dynamic response of a cable-supported structure.